A Comparative Study between Khufu’s First and Second Boats in Respect of Their Materials, Archaeological Conditions, and Conservation - Yoshimura, Kanan (AUC Knowledge Fountain, 2022)
This thesis is a study and comparative analysis of the two large, wooden boats found next to the Giza pyramid of King Khufu, a ruler of ancient Egypt’s Fourth Dynasty, c. 2575-2550 BC. Each boat was found dismantled and buried on the south side of the king’s pyramid in pits 4-meters deep and each was covered with stone slabs. This study will investigate both boats with respect to the carpentry techniques used in their construction; their materials, such as different woods, ropes, mortar, and copper; the meaning of the inscriptions found on each boat; and the deterioration of some parts of the boats due to the environment changes. Because of this deterioration, both boats had to undergo intensive conservation, including work done to bring back the original shape of some important parts of the boats. The first boat was extracted from its pit in the 1950’s and conserved and reconstructed in a process that has been the subject of several books and articles. The second boat has only recently — between 2014 and 2022 — been removed from its pit and conserved by a joint Japanese-Egyptian project, which successfully preserved more than 1800 pieces of ancient wood as well as nearly 100 ancient copper fixtures. The thesis will provide the first detailed description of the Second Khufu Boat Project and of the many years dedicated to preparing for and carrying out the recovery of the second boat. Finally, the thesis will address the construction of such boats as well as the question of why such massive boats were needed to accompany the king to the afterlife.